Science, technology, and society - Prieto, Nelia G.; Vega, Violeta A.;Felipe, Elizabeth F.;Meneses, Julius L. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2019)
This book on Science, Technology and Society, is designed in line with CHED CMO No.20, series of 2013. As an instructional tool, it is meant to "engage students to confront realities brought about by Science, Technology and Society." The book is divided into six chapters with several lessons under each. - - Preface
Chapter I General concepts and historical developments -- Chapter II Science, technology and society and the human condition -- Chapter III Specific issues in STS -- Chapter IV Climate change and energy crisis -- Chapter V Environmental awareness -- Chapter VI Alternative energy resources.
Includes bibliographical references.
Keywords: SCIENCE AND TECHNOLOGY